2020
DOI: 10.3389/fpsyt.2020.00789
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Developments in Human Induced Pluripotent Stem Cell-Derived Microglia: Implications for Modelling Psychiatric Disorders With a Neurodevelopmental Origin

Abstract: Microglia, the resident tissue macrophages of the brain, are increasingly implicated in the pathophysiology of psychiatric disorders with a neurodevelopmental origin, including schizophrenia. To date, however, our understanding of the potential role for these cells in schizophrenia has been informed by studies of aged post-mortem samples, low resolution in vivo neuroimaging and rodent models. Whilst these have provided important insights, including signs of the heterogeneous nature of microglia, we currently l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 133 publications
(239 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, recent data from a mouse model of MIA provides evidence that IL-6 increases microglial motility in vivo (Ozaki et al, 2020). Based on these data we acquired live cell imaging data to record the effect of 3h exposure to IL-6 (100 ng/ml) on MGL whole cell (nuclear) motility, cytoplasmic specific (cytoplasm) motility and morphology, another known correlate of microglial function (Hanger et al, 2020). We observed that vehicle treatment was by itself sufficient to influence MGLs motility, as evidenced by an increase in cytoplasmic distance and displacement in both vehicle-and IL-6 treated cultures relative to untreated controls ( Figure 4A , statistics in Supplementary Table 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent data from a mouse model of MIA provides evidence that IL-6 increases microglial motility in vivo (Ozaki et al, 2020). Based on these data we acquired live cell imaging data to record the effect of 3h exposure to IL-6 (100 ng/ml) on MGL whole cell (nuclear) motility, cytoplasmic specific (cytoplasm) motility and morphology, another known correlate of microglial function (Hanger et al, 2020). We observed that vehicle treatment was by itself sufficient to influence MGLs motility, as evidenced by an increase in cytoplasmic distance and displacement in both vehicle-and IL-6 treated cultures relative to untreated controls ( Figure 4A , statistics in Supplementary Table 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple lines of evidence from human genetics, post-mortem , neuroimaging and peripheral biomarker studies implicate the innate immune system and particularly microglia in the pathophysiology of neuropsychiatric disorders ( Mondelli et al, 2017 ). As the resident CNS myeloid cells, microglia play critical roles in shaping the central immune response to maintain homeostasis ( Hanger et al, 2020 ). The disturbance of healthy microglial function by MIA during foetal brain development could, in turn, disrupt essential processes required for healthy foetal or adult neurogenesis and neural circuit formation ( Knuesel et al, 2014 ).…”
Section: Prenatal Immune Challenge Alters Hippocampal Neurogenesismentioning
confidence: 99%
“…Microglia are highly plastic cells, which can assume a range of functional and morphological states, resulting in significant intra- and inter-regional heterogeneity in the brain ( Hanger et al, 2020 , Sharma and Tremblay, 2020 ). Microglia polarised to a pro-inflammatory state release reactive oxygen species, complement proteins, proteinases and pro-inflammatory cytokines such as IL-6, TNFα, IL-1β, which attract other immune cells, such as macrophages, dendritic cells and lymphocytic T-cells, facilitating their entry into the brain across the blood–brain barrier and promoting phagocytosis of foreign agents or neurotoxic cellular debris ( Barres, 2008 , Hanger et al, 2020 ). These actions can impede the neurogenic cascade during chronic stress ( Sierra et al, 2014 ).…”
Section: Prenatal Immune Challenge Alters Hippocampal Neurogenesismentioning
confidence: 99%
“…However, despite these challenges, we succeeded in generating complete gene knockout cell lines for each of the selected gene targets, providing a reliable and potentially scalable in vitro platform at a relatively low cost. Additionally, these protocols are now optimized and can be readily adapted to create a potent pharmacological tool to gain mechanistic insights on the pharmacology of both old and new drug targets [38].…”
Section: Targeting Drd3 and Htr1a Genes To Study The Effects Of Buspirone In Microglial Cellsmentioning
confidence: 99%